Caregiving and Friendship: Perspectives From Care Partners of People With Aphasia. Issue 1 (January 2023) - Madden, Elizabeth B.; Therrien, Michelle; Bislick, Lauren; Wallace, Sarah E.; Goff-Albritton, Rachel; Vilfort-Garces, Ana; Constantino, Christopher; Graven, Lucinda
Abstract : Friendship is an essential component of quality of life. The ongoing lifestyle changes and strain typically experienced by care partners of people with aphasia (PWA) can impact their social network, with friendships being particularly vulnerable to change. This study aimed to understand the impact of caregiving on care partners' friendships over time from the perspective of care partners of PWA. An online survey addressing care partners' demographics, care recipients' demographics, and care partners' perceptions of their friendships over time (before caregiving and during the acute and chronic stages of caregiving) was codesigned with three care partner stakeholders and then distributed to other individuals who care for a person with aphasia. Survey responses from 35 care partners of PWA who completed the survey were analyzed using quantitative and qualitative methods. Most participants reported their friendships were different in both the acute and chronic stages of caregiving compared with before caregiving. Overall, perceived friendship satisfaction and support decreased over time. Qualitative analysis revealed five main factors that could either facilitate or hinder care partner friendships, including role changes, personal characteristics, friendship initiation, friendship interactions, and outside influences. This work highlights that caring for a loved one with aphasia negatively impacts friendships for many care partners, and these friendship changes are often long-lasting. More resources for managing the impact of aphasia on care partners' social lives are needed, which, in turn, might improve the friendships and well-being of both the care partner and their loved one with aphasia.